Migration, Gender, and Integration: Syrian Women's Experiences in Türkiye - Yanik Aslan, Sibel (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2025)
The global phenomenon of migration in the 21st century, often referred to as the "Age of Migration," is characterized by the increasing feminization of migratory flows and the growing recognition of women's distinct experiences within these processes. In the context of Syria, prolonged conflict and displacement have rendered women particularly vulnerable, yet have also positioned them as active agents in survival and integration processes within host societies such as Türkiye. This study examines the influence of gender on the social, economic, and cultural integration of Syrian women residing in Türkiye under temporary protection. It aims to elucidate the intersection of forced migration, gender norms, and integration dynamics, with a particular focus on the duality of vulnerability and resilience that characterizes the lived experiences of these women. Utilizing a qualitative methodology, this study integrates data from non-governmental organizations and institutional reports, survey results, and extant academic literature. Employing a feminist analytical framework, specifically the theory of the feminization of migration, the article explores the multifaceted dimensions of women's adaptation, encompassing legal status, employment, education, and social participation. The findings indicate that the integration of Syrian women in Türkiye is hindered by patriarchal structures, temporary legal status, and socio-cultural barriers, while also being influenced by their agency and adaptive strategies. The study contends that integration policies lacking a gender-sensitive perspective perpetuate dependency and social exclusion. A comprehensive, rights-based, and gender-inclusive framework is crucial for fostering women's empowerment, strengthening social cohesion, and promoting sustainable integration between migrant and host communities. [Fenomena global migrasi pada abad ke-21, yang sering disebut sebagai “Era Migrasi”, ditandai oleh meningkatnya feminisasi arus migrasi serta semakin besarnya pengakuan terhadap pengalaman khas perempuan dalam proses tersebut. Dalam konteks Suriah, konflik berkepanjangan dan situasi pengungsian telah menjadikan perempuan berada dalam posisi yang sangat rentan, namun sekaligus menempatkan mereka sebagai aktor aktif dalam proses bertahan hidup dan integrasi di masyarakat penerima, seperti Türkiye. Penelitian ini mengkaji pengaruh gender terhadap integrasi sosial, ekonomi, dan budaya perempuan Suriah yang tinggal di Türkiye di bawah status perlindungan sementara. Penelitian ini bertujuan untuk menjelaskan irisan antara migrasi paksa, norma-norma gender, dan dinamika integrasi, dengan menitikberatkan pada dualitas kerentanan dan resiliensi yang mewarnai pengalaman hidup perempuan Suriah tersebut. Dengan menggunakan metode kualitatif, penelitian ini mengintegrasikan data yang bersumber dari organisasi non-pemerintah dan laporan institusional, hasil survei, serta literatur akademik yang relevan. Melalui kerangka analisis feminis, khususnya teori feminisasi migrasi, artikel ini mengeksplorasi dimensi-dimensi adaptasi perempuan secara multidimensional, yang mencakup status hukum, ketenagakerjaan, pendidikan, dan partisipasi sosial. Temuan penelitian menunjukkan bahwa integrasi perempuan Suriah di Türkiye terhambat oleh struktur patriarkal, status hukum yang bersifat sementara, serta berbagai hambatan sosial dan kultural, namun pada saat yang sama juga dipengaruhi oleh agensi dan strategi adaptif yang mereka kembangkan. Studi ini berpendapat bahwa kebijakan integrasi yang tidak memiliki perspektif sensitif gender cenderung mereproduksi ketergantungan dan eksklusi sosial. Oleh karena itu, diperlukan suatu kerangka kerja yang komprehensif, berbasis hak asasi manusia, dan inklusif gender untuk mendorong pemberdayaan perempuan, memperkuat kohesi sosial, serta mempromosikan integrasi yang berkelanjutan antara komunitas migran dan masyarakat penerima.]